(untitled) (Fiep Bulletin - online, 2011)
Introduction: AIDS currently accounts for a major challenge to research, treatment and clinical and social intervention. The quality of care is an important determinant of the success of programs aimed at chronic disease like AIDS; it causes an impact on quality of life of patients. Objective: To know the perception of professionals in a reference center for AIDS treatment, care about the needs of people with HIV. Methodology: This is a qualitative research, developed at the Hospital Giselda Trigueiro (HGT), located in Natal -RN/Brazil. The population consisted of 15 professionals who work with children and adolescents living with HIV in that center. Data collection, which occurred in the period between March and June 2006, using a structured interview with structured questions, validated through a pilot study. The data were analyzed by analysis of thematic categories. Results: The categories that emerged from the discourse of interviewees in relation to the care needs of patients and HIV were: improvement of symptoms, compliance with drug therapy, and well - being of the client. Conclusion: It is expected that the discussion of this issue will contribute to a better understanding of the complexity involved in AIDS in childhood and adolescence, and that encourages practitioners to use approaches guided the sensitivity to fully meet the needs of those living with the particular HIV/AIDS.